Factors contributing to the high prevalence of multidrug-resistant tuberculosis: a study from China. Issue 7 (8th March 2012) - Liang, Libo; Wu, Qunhong; Gao, Lijun; Hao, Yanhua; Liu, Chaojie; Xie, Yanguang; Sun, Hong; Yan, Xinglu; Li, Fabin; Li, Honghai; Fang, Hongxia; Ning, Ning; et al.
Abstract : Background: The rapid spread of multidrug-resistant tuberculosis (MDR-TB) has attracted global concerns. This study aimed to identify factors contributing to the high prevalence of MDR-TB in China's Heilongjiang province. Methods: A cross-sectional survey following the WHO/International Union Against Tuberculosis and Lung Disease guidelines was conducted with consecutive recruitment of patients with TB in 30 counties selected at random in Heilongjiang in 2004. A total of 1995 patients were tested for MDR-TB. Factors associated with MDR-TB were identified through multilevel models and traditional logistic regression analysis, along with in-depth interviews with nine patients, five healthcare managers and four doctors. Results: 241 patients (12%) were identified with MDR-TB. The retreatment patients were 5.48 times (95% CI 4.04 to 7.44) more likely to have MDR-TB than newly diagnosed patients. The patients who were treated with isoniazid and rifampin for >180 days were 4.82 times (95% CI 2.97 to 7.81) more likely to develop MDR-TB than those treated <180 days. Age and delay in initiating TB treatment were associated with MDR-TB. Financial burden, poor knowledge and side effects of TB treatment were perceived by the interviewees as influencing factors. Lack of coordination of services, unsatisfactory supervision of treatment and infection control jeopardised the control of MDR-TB. Conclusions: Inappropriate treatment is the most important influencing factor of MDR-TB. Increasing people's awareness of TB, early detection and appropriate treatment of patients with TB should become a priority, which requires strong commitment and collaboration among health organisations and greater compliance with TB treatment guidelines by service providers and patients.